Epimeria (Pseudepimeria) callista d'Acoz & Verheye 2017, sp. nov. - d'Acoz, Cédric d'Udekem; Verheye, Marie L. (Zenodo, 2017)
Epimeria ( Pseudepimeria ) callista sp. nov. urn:lsid:zoobank.org:act: 8E717EF2-0CC3-4796-859D-90F60B661961 Figs 257–264 Epimeria grandirostris – Bellan-Santini, 1972: 223. ‘Clade H grandirostris-pulchra-oxicarinata complex - GR2ʹ – Verheye et al. 2016a, supplement: 5 (online). non Pseudepimeria grandirostris Chevreux, 1912: 216. Etymology From the Greek, καλλιστος, Latinized as callistus , -a , -um , adjective meaning very beautiful, the most beautiful. Type material Holotype RV Aurora Australis cruises: SOUTHERN OCEAN: adult ♀, cruise CEAMARC, sample CEAMARC 3978, stn 36EV297, Adélie Coast, 66°20ʹ20″ S, 143°41ʹ08″ E, 552–573 m, beam trawl, 4 Jan. 2008, coll. IPEV-AAD-MNHN (MNHN-IU-2014-7336, removed from MNHN-IU-2014-4327) [Extraction P40; Genbank nr, 28S: KU759683]. Paratypes RV Aurora Australis cruises: SOUTHERN OCEAN: 1 dissected adult ♀, cruise CEAMARC, sample CEAMARC 3978, stn 36EV297, Adélie Coast, 66°20ʹ20″ S, 143°41ʹ08″ E, 552–573 m, beam trawl, 4 Jan. 2008, coll. IPEV-AAD-MNHN, (MNHN-IU-2014-7337, removed from MNHN-IU-2014-4327). RV Seatruck cruises: SOUTHERN OCEAN: 1 small and damaged spec., cruise REVOLTA II, stn REVO_029, Collect_ID: REVO_183, Adélie Coast, 66°39ʹ30″ S, 140°01ʹ59″ E, 97–103 m, beam trawl, 26 Jan. 2011, coll. N. Améziane, N. Bax, C. Gallut, A.C. Lautrédou and C. Robineau (MNHN-IU-2014-4300). Description ROSTRUM. Long, overreaching tip of peduncle of antenna 1; in lateral view, regularly curved along all its length, not forming an angle with head, ventrally straight, tip not abruptly curving downwards; in frontal view, fairly narrow, with weakly convex borders, with acute tip. EYE. Medium-sized, conical. PEREION–PLEOSOME TOOTH PATTERN. Pereionite 1 with low, very broad, rounded mid-dorsal tooth of which the anterior border is very oblique, with pair of well-developed, rounded, dorsolateral teeth and pair of small ventrolateral teeth; pereionite 2 much narrower than pereionites 1 and 3, with small broad rounded tooth pointing upwards (as high as mid-dorsal tooth of pereionite 1 and ...